Independent biodiversity mechanisms regulate ecosystem multifunctionality and its temporal stability under resource enrichment in a mown grassland - Xu, Fengwei; Li, Jianjun; Wu, Liji; Su, Jishuai; Zhu, Biao; Wang, Yang; Chen, Dima; Bai, Yongfei (Journal of vegetation science, 2024)
Questions Although the relationships between biodiversity and individual ecosystem functions under resource enrichment have been extensively studied, there is limited understanding of how resource‐induced changes affect ecosystem multifunctionality and its temporal stability, along with the underlying biological mechanisms. Location Inner Mongolia, China. Methods We investigated the impact of biodiversity mechanisms on ecosystem multifunctionality and its temporal stability through a 3‐year field experiment. This experiment involved augmenting growing season precipitation and nitrogen deposition, conducted in a typical steppe ecosystem of Inner Mongolia alongside regular mowing. Results Our findings revealed that the addition of water (W) and nitrogen (N) had varying effects on ecosystem multifunctionality and its temporal stability. The combination of N and W additions enhanced ecosystem multifunctionality, whereas both W and N + W additions promoted the temporal stability of ecosystem multifunctionality. Structural equation modeling demonstrated that the community‐weighted mean height, in response to nitrogen addition, played a key role in enhancing ecosystem multifunctionality. By contrast, increased species asynchrony because of water addition and greater functional diversity in terms of leaf area contributed to heightened temporal stability of ecosystem multifunctionality. Furthermore, the positive effects of community‐weighted mean height on ecosystem multifunctionality exhibited a gradual increase with rising threshold levels. Conclusions Our study provides the first evidence of the independent effects of selection, exemplified by community‐weighted mean and complementarity, represented by factors such as species richness, functional diversity and species asynchrony on both ecosystem multifunctionality and its temporal stability. This underscores how global change factors can directly influence ecosystem multifunctionality and its temporal stability while also indirectly modulating biodiversity effects in the short term. Overall, our findings underscore the vital role of biodiversity conservation in enhancing grassland management and the delivery of ecosystem services in the context of global change, particularly in regions subject to extensive mowing. We determined the pattern and biodiversity drivers of ecosystem multifunctionality and its temporal stability responses to resource input in a mown Inner Mongolia grassland. Input of different resource types had varying effects on ecosystem multifunctionality and its temporal stability. Further, our study provides the first evidence of the independent effects of selection and complementarity on ecosystem multifunctionality and its temporal stability.